Management of thrombotic and obstetric antiphospholipid syndrome: a systematic literature review informing the EULAR recommendations for the management of antiphospholipid syndrome in adults - Angela Tincani; Michael M Ward; Marteen Limper; Maria G Tektonidou; Laura Andreoli (RMD Open)
Objective To perform a systematic literature review (SLR) informing the European Lmmendations for the management of antiphospholipid syndrome (APS) in adults.Methods A SLR through January 2018 was performed. Research questions were constructed using the Patient, Intervention, Comparator, Outcome (PICO) format. We included data from articles that reported on each relevant intervention. Summary effect estimates were calculated for direct comparison studies that matched the PICO question exactly, and for studies with the relevant intervention and comparator. When meta-analyses were available, we used these estimates.Results From 7534 retrieved articles (+15 from hand searches), 188 articles were included in the review. In individuals with high-risk antiphospholipid antibody (aPL) profile without prior thrombotic or obstetric APS, two meta-analyses showed a protective effect of low-dose aspirin (LDA) against thrombosis. Two randomised controlled trials (RCTs) and three cohort studies showed no additional benefit of treatment with vitamin K antagonists at target international normalised ratio (INR) 3–4 versus INR 2–3 in patients with venous thrombosis. In patients with arterial thrombosis, two RCTs and two cohort studies showed no difference in risk of recurrent thrombosis between the two target INR groups. One open-label trial showed higher rates of thrombosis recurrences in triple aPL-positive patients treated with rivaroxaban than those treated with warfarin. RCTs and cohort studies showed that combination treatment with LDA and heparin was more effective than LDA alone in several types of obstetric APS. SLR results were limited by the indirect evidence and the heterogeneity of patient groups for some treatments, and only a few high-quality RCTs.Conclusion Well-designed studies of homogeneous APS patient populations are needed.